Sex-specific differences in hypertension - T. O. Brodovskaya; D. V. Kasyanov (Российский кардиологический журнал)
The diagnosis of hypertension (HTN) has been known to doctors for many years. Current clinical guidelines represent a unified approach to the treatment and prevention of hypertension in patients of both sexes. Meanwhile, there are data that the development, course, progression and treatment of the disease may differ depending on sex. The aim of the review was to systematize modern ideas about sex differences in hypertension, as well as to substantiate the differentiated treatment among men and women. A literature search for 2013-2023 was conducted in the PubMed, Cochrane Library, Embase, Google Scholar, eLibrary databases using the search phrase "sex differences in hypertension". This work reflects current data regarding sex-specific differences in hypertension, including its development, blood pressure regulation, sex characteristics of risk factors, target organ damage, and features of antihypertensive treatment. Differentiated approach considering sex differences may provide novel strategies for preventing the progression of cardiovascular disease.